Environmental & architectural phenomenology. Vol. 9, issue 3 - (:unkn) unknown (Kansas State University. Architecture Department, 1998)
Vol. 9, No. 3, Fall 1998 (includes “items of interest,” "citations received,” book review of Rachel Kaplan, Stephen Kaplan & Robert L. Ryan's With People in Mind, and essays by Thomas Erickson & Ian Lambert).
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals